A systematic PCR-based framework for amplification of long and multi-exonic genes in non-model insects: : A case study of Bemisia tabaci Asia II 1 - C. N. Rajarushi; Amit Umesh Paschapur; Sai Manoj Marella; Muthuganeshan Annamalai; J. S. Pavan; Arunesh Kumar; Ramcharan Bhattacharya; Sabtharishi Subramanian (Molecular Biology Reports, 2026)

Integrative quantum and systems biology of cancer: From molecular fluctuations to ecological outcomes - Matheus C. Casotti; Bárbara C. Ferreira; Bianca P. Campanharo; Camilly V. Campanharo; Carolina de S.C. Delfino; Cezar A.F. Teixeira; Fellipe Pesente; Isabele P. Pavan; Júlia de O. Machado; Lorena S.R. Mauricio; Lorrayne E.S. de B. Campos; Luíza S.B. de B. Góes; et al. (BioSystems, 2026)

Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Linear quaternion interpolation reveals globally consistent closed-circuit point cloud registration - Rubens A. L. Benevides; Daniel R. dos Santos; Nadisson L. Pavan; Henrique C. de Oliveira; Humberto Diego A. Alves (Applied Geomatics, 2026)
In the task of 3D environment mapping from point cloud registration, we face the problem of global consistency analysis in the presence of noises and a low overlap rate. Significant errors in the registration result in less consistent environment maps. This study aims to present a linear interpolation method for consistent terrestrial laser scanning data registration to overcome the drift problem from pairwise registration errors, taking advantage of loop closing detection into a circuit. A coarse-to-fine point cloud registration is constructed beforehand. Then, a linear interpolation approach is proposed to redistribute the registration errors further without constraints globally. Compared with the mainstream point cloud registration algorithm, the proposed method shows the highest global consistent accuracy in different scenarios. Our method achieves state-of-the-art with global registration accuracy within 5 mm, sufficient to create compatible 3D maps.

Butyrate antagonizes Annexin A2–mediated tauopathy via Annexin A1 reciprocity in Alzheimer's disease - Pavan K. Jayaswamy; Trupthi Ambrish; Vinay C. Sangamesh; Adithi Kellarai; Prakash Patil; Lobo Manuel Alexander; Praveenkumar Shetty (Food and Chemical Toxicology, 2026)

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

Immune profiling of human blood cells after indirect exposure to crystalline silica particles - Evangel Kummari; Anja Bråthen Kristoffersen; Sabin Bhandari; Hege Hjertholm; Hubert Dirven; Sarah E. Josefsson; François Huaux; Riccardo Leinardi; Cristina Pavan; Manosij Ghosh; Peter Hoet; Unni C. Nygaard; et al. (Environmental Research, 2026)

Gut microbiota-mediated nitrogen recycling in the white Grub Holotrichia longipennis: A model for microbiome-targeted pest control - J. S. Pavan; P. M. Deeksha; C. N. Rajarushi; Amit Umesh Paschapur; K. S. Rishika; Balasubramanian Ramakrishnan; Sabtharishi Subramanian (World Journal of Microbiology and Biotechnology, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Antagonistic Regulation of Pro-Inflammatory AnnexinA2 and Anti-Inflammatory AnnexinA1 in the Pathogenesis of Idiopathic Pulmonary Fibrosis - Vinay C Sangamesh; Pavan K Jayaswamy; Yashodhar Prabhakar Bhandary; Fathimath Muneesa Moideen; Giridhar B H; Jayaprakash Shetty K; Prakash Patil; Rekha Koravadi Narasimhamurthy; Amod Kulkarni; Praveenkumar Shetty (Cell Biochemistry and Biophysics, 2025)

India leads in emission intensity per GDP: Insights from the gridded emission inventory for residential, road transport, and energy sectors - Viswanath Velamuri; Diljit Kumar Nayak; Shubham Sharma; Pareshbhai Dineshbhai Parmar; Pavan Kumar Nagar; Dhirendra Singh; Mukesh Sharma; Yash Jain; Arpit Katiyar; Sunil Dahiya; Nandikesh Sivalingam; Lauri Myllyvirta; et al. (Journal of Environmental Sciences, 2025)

Targeted delivery aspects of proanthocyanidins in breast cancer treatment: from discovery to development - Krishna Kuna; Seshadri Nalla; Jailani Shiekmydeen; Pavan C. Akkiraju; Mahesh P. More; Srinivas Ganta; Srinivas Enaganti; Rahul S. Tade (Molecular and Cellular Biochemistry, 2025)

Study on the Antifibrotic Property of Biogenic Zinc Oxide Nanoparticles Using Coriolus versicolor in the Rat Liver Failure Model - Remya M.; Raguvaran R.; Siddharth Chaudhary; Karikalan M.; Haritha C. V.; Madhu C. L.; Abhishek Chandra Saxena; Vadapalli Deekshita; Nerella Venkata Pavan Kumar; Shanmugarathinam A. (Biological Trace Element Research, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

P30-49 Hazard assessment of endocrine disruption potential using new alternative methods: integration of in vitro thyroid peroxidase inhibition potency and metabolic fate of 3-amino-2,6-dimethylphenol explains its lack of thyroid toxicity in vivo - K.C. Fussell; S. Verkaart; J. van den Elzen; N. Pineiro Costas; M. Pavan; C. Novello; B. Blömeke; M. Wenker; C. Goebel (Toxicology Letters, 2025)

P28-31 Diverging endocrine disruption potential of resorcinol and paracetamol: profiling the endocrine disruption potential of these compounds and their metabolites using in silico methods - C. Novello; M. Pavan; K. Fussell; C. Goebel (Toxicology Letters, 2025)

P28-18 Diverging endocrine disruption potential of resorcinol and paracetamol: thyroid peroxidase inhibition potency and metabolic fate differences under pharmaceutical and cosmetic use explain their contrasting endocrine disruption capabilities - K.C. Fussell; S. Verkaart; J. van den Elzen; M. Pavan; C. Novello; B. Blomeke; M. Wenker; C. Goebel (Toxicology Letters, 2025)

Protective Role of Green-Synthesized Zinc Oxide Nanoparticles Against Prenatal Ethion Toxicity in Rats - Nerella Venkata Pavan Kumar; V. A. Aneesha; Elizabeth Glanet Durom; M Remya; M. Karikalan; R. Raguvaran; Madhu C. Lingaraju; Subhashree Parida; Avinash G. Telang; Thakur Uttam Singh (Biological Trace Element Research, 2025)

AnxA2-EGFR pro-inflammatory signaling potentiates EMT-induced fibrotic stress and its modulation by short-chain fatty acid butyrate in idiopathic pulmonary fibrosis - Vinay C. Sangamesh; Pavan K. Jayaswamy; Vijay M. Krishnaraj; Nithin K. Kuriakose; Giridhar B. Hosmane; Jayaprakash K. Shetty; Prakash Patil; Sukanya Shetty; Roopa Bhandary; Praveenkumar Shetty (Toxicology and Applied Pharmacology, 2025)

Evaluating TGF-β1 gene expression and promoter polymorphism in cervical cancer progression - Pavan Kumar Poleboyina; Akbar Pasha; S. K. Heena; Sneha Malleswari Poleboyina; Smita C. Pawar (Journal of Molecular Histology, 2025)

Targeting AnxA2-EGFR signaling: hydroxychloroquine as a therapeutic strategy for bleomycin-induced pulmonary fibrosis - Vinay C. Sangamesh; Dhananjay B. Alagundagi; Pavan K. Jayaswamy; Nithin Kuriakose; Praveenkumar Shetty (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Bats (Mammalia: Chiroptera) of Ubajara National Park, Ceará, Brazil: a diversity assessment using complementary sampling methods - Ana C. Pavan; Gustavo L. Urbieta; Werther P. Ramalho; Gabryella S. Mesquita; Jeanneson Sales; Fábio Falcão; Tarcilla Valtuille (Mammal Research, 2024)

P13-09 Data collection for the compilation of the EFSA pesticides genotoxicity database in IUCLID - C. Novello; A. Bassan; M. Castoldi; M. Pavan; O. Tcheremenskaia; J.M. Parra Morte (Toxicology Letters, 2024)

A Pilot Study Based on the Correlation Between Whole Exome and Transcriptome Reveals Potent Variants in the Indian Population of Cervical Cancer - Santosh Kumari Duppala; Pavan Kumar Poleboyina; Bhumandeep Kour; Govardhan Bale; Ashish Vyas; Smita C. Pawar; Prashanth N. Suravajhala; Sugunakar Vuree (Indian Journal of Microbiology, 2024)

Prenatal exposure to ethion caused maternal and foetal toxicity in rats - Elizabeth Glanet Durom; V.A. Aneesha; Nerella Venkata Pavan Kumar; Ajmi Bin Azeez; M. Karikalan; Madhu C. Lingaraju; Subhashree Parida; Avinash G. Telang; Thakur Uttam Singh (Reproductive Toxicology, 2024)

Morphological and genetic diversity in a South American forest‐dependent bat - Sofia Marques Silva; Ana Carolina Pavan; Samara Alves Barroso de Souza; Gilmax Gonçalves Ferreira; José de Sousa e Silva; Leonardo C. Trevelin (Zoologica Scripta, 2024)
The Neotropical realm is vastly known for its richness, being the Amazon one of the main cradles of taxonomic diversity in the region. In the last decades, molecular analyses have been further increasing the number of Amazonian vertebrate species, hidden under traditional taxonomy due to morphological convergence. Bats represent an interesting example, as the number of recognized bat species is continuously expanding with the identification of numerous cryptic taxa. Studies combining different lines of evidence, such as morphometric and molecular approaches, have been playing an important role in addressing knowledge gaps on Neotropical bat diversity. Within the Phyllostomidae family, the dwarf little fruit bat Rhinophylla pumilio is a forest‐dependent species, with a disjunct distribution in the Amazonian and Atlantic forests. Moreover, different karyotypes have been recovered across the species distribution, suggesting this might be one more example of cryptic diversity. Here, we test this assumption by identifying geographic patterns of morphological and molecular variation within the species' entire range of distribution. Our results point to an overall morphological and morphometric homogeneity, except between Atlantic Forest and Amazonian specimens, with significant dissimilarity among some cranial characters. Furthermore, genetic data suggest a rapid and recent diversification, with these two lineages most likely corresponding to speciating taxa. Within the Amazonian forest, our molecular analyses also recovered four additional lineages, likely encompassing intraspecific diversity. Furthermore, studies are required to confirm the need for a taxonomic rearrangement.

LP-37: Data mining to support food safety assessment - A. Bassan; F. Callà; M. Castoldi; C. Novello; M. Pavan (Toxicology Letters, 2023)

LP-20: How can in silico methods support the derivation of safety limits? - C. Novello; A. Bassan; M. Pavan (Toxicology Letters, 2023)

P17-03: Gasdermin D pores orchestrate IL-1α secretion from macrophages exposed to nearly free silanols (NFS)-rich silica particles - R. Leinardi; A. Pochet; F. Uwambayinema; Y. Yakoub; V. Quesniaux; B. Ryffel; P. Broz; C. Pavan; F. Huaux (Toxicology Letters, 2023)

Racial and ethnic disparities in exposure to risk-screening environmental indicator (RSEI) toxicity-weighted concentrations: Michigan Census Tracts, 2008–2017 - Amanda Pavan; Sue C. Grady; Igor Vojnovic (Journal of Environmental Studies and Sciences, 2023)

Structural and morphological properties of in-situ biosynthesis of biocompatible bacterial cellulose/Laponite nanocomposites - Rafael R. Domeneguetti; Vanessa Y. Sakai; Gustavo F. Perotti; Isabel C. Silva; Agnieszka Tercjak; Hernane S. Barud; Fernando Pavan; Vera R.L. Constantino; Sidney J. Ribeiro (Applied Clay Science, 2023)

Pre-slaughter stress mitigation in goats: Prospects and challenges - Pavan Kumar; Abubakar Ahmed Abubakar; Muideen Adewale Ahmed; Muhammad Nizam Hayat; Ubedullah Kaka; Mirian Pateiro; Awis Qurni Sazili; Louwrens C. Hoffman; Jose M. Lorenzo (Meat Science, 2023)

Notes on Grewia tenax (Forssk.) Fiori: an underutilized multipurpose shrub of hot arid region of western Rajasthan - Anil Patidar; K. Venkatesan; J. P. Singh; Rahul Dev; Pavan Kumar Malav; Mahesh Kumar; S. C. Meena; Archana Sanyal; Mavji Patidar (Genetic Resources and Crop Evolution, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Deep genetic divergence in Randall’s threadfin bream Nemipterus randalli Russell, 1986 population from northern Bay of Bengal inferred by mtDNA sequences - Murugesan SriHari; Annam Pavan-Kumar; Barry C. Russell; Daniel Golani; Zeba Jaffer Abidi; Loveson Edward (Marine Biology Research, 2022)

A study of Palnadu earthquake sequence in the Cuddapah basin and its tectonic implications - D Srinagesh; T C Sunilkumar; B Naresh; S Vitthal; Dhiraj K Singh; Ravi P Singh; Mahalaxmi Naidu; G Suresh; P Solomon Raju; V Pavan Kumar; Prantik Mandal; A N S Sarma (Journal of Earth System Science, 2021)

Charging for water withdrawal in sanitation in Brazilian semi-arid area - Telma C. S. Teixeira; Karine dos S. Veiga; Frank Pavan de Souza; Claudiano C. Cruz Neto; Gleice de S. Aguiar (Sustainable Water Resources Management, 2021)

A note on distribution and potential of Japanese wild adzuki bean [Vigna angularis var. nipponensis (Ohwi) Ohwi and H. Ohashi] in India - K. C. Bhatt; Pavan Kumar Malav; Padmavati G. Gore; Kuldeep Tripathi; R. S. Rathi; Umeshkumar L. Tiwari; S. P. Ahlawat (Genetic Resources and Crop Evolution, 2021)

Gaps Filling in HF Radar Sea Surface Current Data Using Complex Empirical Orthogonal Functions - Siva Srinivas Kolukula; Balaji Baduru; P. L. N. Murty; J. Pavan Kumar; E. Pattabhi Rama Rao; S. S. C. Shenoi (Pure and Applied Geophysics, 2020)

Monitoring adventitious presence of transgenes in brinjal (Solanum melongena L.) collections from the regions in India bordering Bangladesh: a case report - Sahadeo Indaldas Kuwardadra; K. C. Bhatt; Aparna Paliwal; Payal Sood; Pavan Kumar Malav; Kushaldeep Kaur Sodhi; Gurinderjit Randhawa (Genetic Resources and Crop Evolution, 2020)

Removal of pharmaceutical compounds from aqueous solution by novel activated carbon synthesized from lovegrass (Poaceae) - Nilton F.G.M. Cimirro; Eder C. Lima; Mariene R. Cunha; Silvio L. P. Dias; Pascal Silas Thue; Ana C. Mazzocato; Guilherme L. Dotto; Marcos A. Gelesky; Flávio André Pavan (Environmental Science and Pollution Research, 2020)

Removal of amoxicillin from simulated hospital effluents by adsorption using activated carbons prepared from capsules of cashew of Para - Diana Ramos Lima; Eder C. Lima; Cibele S. Umpierres; Pascal Silas Thue; Ghadir A. El-Chaghaby; Raphaelle Sanches da Silva; Flavio A. Pavan; Silvio L. P. Dias; Camille Biron (Environmental Science and Pollution Research, 2019)

Conversion of Eragrostis plana Nees leaves to activated carbon by microwave-assisted pyrolysis for the removal of organic emerging contaminants from aqueous solutions - Mariene R. Cunha; Eder C. Lima; Nilton F. G. M. Cimirro; Pascal S. Thue; Silvio L. P. Dias; Marcos A. Gelesky; Guilherme L. Dotto; Glaydson S. dos Reis; Flávio A. Pavan (Environmental Science and Pollution Research, 2018)

‘Jumin’ a traditional beverage of Nocte tribe in Arunachal Pradesh: an ethnobotanical survey - K. C. Bhatt; Pavan Kumar Malav; S. P. Ahlawat (Genetic Resources and Crop Evolution, 2018)

QTL mapping and analysis of epistatic interactions for grain yield and yield-related traits in Triticum turgidum L. var. durum - Pablo F. Roncallo; Pavan C. Akkiraju; Gerardo L. Cervigni; Viviana C. Echenique (Euphytica, 2017)

Eragrostis plana Nees as a novel eco-friendly adsorbent for removal of crystal violet from aqueous solutions - Augusto Cezar D. Filho; Ana C. Mazzocato; Guilherme L. Dotto; Pascal S. Thue; Flávio A. Pavan (Environmental Science and Pollution Research, 2017)

Human topoisomerase inhibition and DNA/BSA binding of Ru(II)–SCAR complexes as potential anticancer candidates for oral application - Rone A. De Grandis; Mariana S. de Camargo; Monize M. da Silva; Érica O. Lopes; Elias C. Padilha; Flávia A. Resende; Rosângela G. Peccinini; Fernando R. Pavan; Alessandro Desideri; Alzir A. Batista; Eliana A. Varanda (BioMetals, 2017)

Removal of Phenolic Compounds from Aqueous Solutions Using Sludge-Based Activated Carbons Prepared by Conventional Heating and Microwave-Assisted Pyrolysis - Glaydson S. dos Reis; Matthew A. Adebayo; Carlos H. Sampaio; Eder C. Lima; Pascal S. Thue; Irineu A. S. de Brum; Silvio L. P. Dias; Flavio A. Pavan (Water, Air, & Soil Pollution, 2017)

Genetic variation of a global germplasm collection of chickpea (Cicer arietinum L.) including Italian accessions at risk of genetic erosion - C. De Giovanni; S. Pavan; F. Taranto; V. Di Rienzo; M. M. Miazzi; A. R. Marcotrigiano; G. Mangini; C. Montemurro; L. Ricciardi; C. Lotti (Physiology and Molecular Biology of Plants, 2017)

Complete mitochondrial genome of threatened mahseer Tor tor (Hamilton 1822) and its phylogenetic relationship within Cyprinidae family - A. PAVAN-KUMAR; SUDHANSHU RAMAN; PRAKASH G. KORINGA; NAMRATA PATEL; TEJAS SHAH; RAJEEV K. SINGH; GOPAL KRISHNA; C. G. JOSHI; P. GIREESH-BABU; APARNA CHAUDHARI (Journal of Genetics, 2016)

The combined influence of riverine barriers and flooding gradients on biogeographical patterns for amphibians and squamates in south‐eastern Amazonia - Leandro J. C. L. Moraes; Dante Pavan; Maria C. Barros; Camila C. Ribas (Journal of Biogeography, 2016)
Aim Our aim was to investigate how the distance to water (flooding gradients) and riverine barriers (Tapajós and Jamanxim rivers) influence the distributional patterns of amphibian and squamate assemblages in the middle Tapajós River region, south‐eastern Amazonia. We also considered the planned hydroelectric dams on both rivers in reviewing the possible impacts of these factors on the amphibian and squamate assemblages. Location Middle Tapajós River system, south‐eastern Amazonia. Methods We conducted diurnal and nocturnal surveys combining pitfall traps and active searches along both banks of the Tapajós and Jamanxim rivers. We identified specimens using an integrative morphological, acoustic, ecological and molecular approach and evaluated the influence of riverine barriers and distance to water using uni‐ and multivariate ordinations, regressions and ANOVA . Results We found changes in species composition for both groups along the flooding gradient and differential riverine barrier effects. The rivers restricted the distribution of 33% of the amphibian species and 8% of the squamates. For amphibians, the main distributional barrier was the Tapajós River, while for squamates both rivers were of similar importance. The assemblages most affected by riverine barriers were non‐riparian amphibians and squamates, as well as riparian amphibians associated with small streams. The functional groups most affected were small, diurnal terrestrial amphibians and small–medium, diurnal partly tree‐dwelling squamates. Main conclusions The Tapajós River is a distributional boundary for lineages centred in western and eastern Amazonia. The fact that many taxa occur on both banks suggests that the Tapajós is a recent or semi‐permeable barrier, while the Jamanxim is an even more recent or weaker barrier. Anthropogenic activities that affect water level, flooding cycles and river flow may influence these natural patterns and cause changes to the equilibrium of the riverine barrier effect. Studies seeking to identify these influences should focus on the most affected functional groups.

SNP mining in transcripts and concomitant estimation of genetic variation in Macrobrachium rosenbergii stocks - Deepak Agarwal; Nilav Aich; A Pavan-Kumar; Sujit Kumar; Supriya Sabnis; C. G. Joshi; Prakash Koringa; Dipal Pandya; Namrata Patel; Tanvi Karnik; Ridhima Bhingarde; P Gireesh-Babu; et al. (Conservation Genetics Resources, 2016)

Meteorological drought analysis over India using analytical framework on CPC rainfall time series - C. S. Murthy; Jyoti Singh; Pavan Kumar; M. V. R. Sesha Sai (Natural Hazards, 2016)

Spatial and temporal variations of total electron content (TEC) and outgoing longwave radiation (OLR) during the period of greater earthquakes near the Indian subcontinent - C. Prasanna Simha; Annam Navaneeth; K. M. Rao; B. K. Rastogi; G. Pavan Kumar; P. Mahesh; V. N. Sridhar; A. K. Shukla (Natural Hazards, 2016)

Morphological variability in holy basil (Ocimum tenuiflorum L.) from India - Pavan Malav; Anjula Pandey; K. C. Bhatt; S. Gopala Krishnan; I. S. Bisht (Genetic Resources and Crop Evolution, 2015)

Enhancements in nocturnal surface ozone at urban sites in the UK - Pavan S. Kulkarni; D. Bortoli; A. M. Silva; C. E. Reeves (Environmental Science and Pollution Research, 2015)

Seismicity of Northwestern Italy during the last 30 years - D. Scafidi; S. Barani; R. De Ferrari; G. Ferretti; M. Pasta; M. Pavan; D. Spallarossa; C. Turino (Journal of Seismology, 2015)

Statistically downscaled climate change projections of surface temperature over Northern Italy for the periods 2021–2050 and 2070–2099 - R. Tomozeiu; G. Agrillo; C. Cacciamani; V. Pavan (Natural Hazards, 2014)

Ionospheric disturbances with the time of occurrence, magnitude and location of the earthquake (M6.5) near the Indian subcontinent - C. P. Simha; G. Pavan Kumar; P. Mahesh; A. Navaneeth; K. M. Rao; B. K. Rastogi; V. N. Sridhar; A. K. Shukla (Natural Hazards, 2014)

Development and Validation of a Spectrofluorimetric Method for the Determination of Erlotinib in Spiked Human Plasma - Bivash Mandal; Pavan Balabathula; Nivesh Mittal; George C. Wood; Himanshu Bhattacharjee (Journal of Fluorescence, 2012)

Establishment and maintenance of persistent infection by picobirnavirus in greater rhea (Rhea Americana) - Gisela Masachessi; Laura C. Martinez; Balasubramanian Ganesh; Miguel O. Giordano; Patricia A. Barril; Maria B. Isa; Alejandro Ibars; Jorge V. Pavan; Silvia V. Nates (Archives of Virology, 2012)

Tropospheric ozone variability over the Indian coastline and adjacent land and sea - Pavan S. Kulkarni; Sachin D. Ghude; S. L. Jain; B. C. Arya; P. K. Dubey; Shahnawaz (International Journal of Remote Sensing, 2011)

Indigenous design and development of a micro-pulse lidar for atmospheric studies - P. K. Dubey; S. L. Jain; B. C. Arya; Y. N. Ahammed; Arun Kumar; D. K. Shukla; Pavan S. Kulkarni (International Journal of Remote Sensing, 2011)

Investigation of foot plantar pressure: experimental and numerical analysis - A. N. Natali; A. Forestiero; E. L. Carniel; P. G. Pavan; C. Dal Zovo (Medical & Biological Engineering & Computing, 2010)

Global distribution of tropospheric ozone and its precursors: a view from space - Sachin D. Ghude; Pavan S. Kulkarni; G. Beig; S. L. Jain; B. C. Arya (International Journal of Remote Sensing, 2010)

On some aspects of tropospheric ozone variability over the Indo-Gangetic (IG) basin, India - Pavan S. Kulkarni; S. L. Jain; Sachin D. Ghude; B. C. Arya; P. K. Dubey; Shahnawaz (International Journal of Remote Sensing, 2009)

Daily precipitation observations over Emilia‐Romagna: mean values and extremes - V. Pavan; R. Tomozeiu; C. Cacciamani; M. Di Lorenzo (International Journal of Climatology, 2008)
Daily precipitation data from a dense observational network covering Emilia‐Romagna, a region of Northern Italy, are described and analysed. Data are available for all stations for the period 1951–2004 and for a selected group of stations located over the Reno hydrological basin for the period 1925–2004. Indices describing seasonal values of mean precipitation and frequency of extreme events are computed starting from daily data and are used to describe the temporal and spatial variability of precipitation over the region. Data referring to the period 1951–2004 are used to describe trends of relevant precipitation indices over the same period in all seasons, and the relation between the variability of these indices and major Euro‐Atlantic large‐scale circulation indices over winter. Data referring to the period 1925–2004 are used to analyse the decadal and long‐term variability over the Reno Basin and its relation with the winter daily discharge of the river. This analysis allows identifying the presence of a clear decadal periodicity in river discharge, strongly related with the decadal variability in both total precipitation and frequency of intense events. Copyright © 2008 Royal Meteorological Society

Climate change scenarios for surface temperature in Emilia-Romagna (Italy) obtained using statistical downscaling models - R. Tomozeiu; C. Cacciamani; V. Pavan; A. Morgillo; A. Busuioc (Theoretical and Applied Climatology, 2007)

Standing-up exerciser based on functional electrical stimulation and body weight relief - M. Ferrarin; E. E. Pavan; R. Spadone; R. Cardini; C. Frigo (Medical & Biological Engineering & Computing, 2002)

Rapid transformations of plant water-soluble organic compounds in relation to cation mobilization in an acid Oxisol - J. C. Franchini; F. J. Gonzalez-Vila; F. Cabrera; M. Miyazawa; M. A. Pavan (Plant and Soil, 2001)

Isolation, genomic organization, and expression analysis of Men1, the murine homolog of the MEN1 gene - Siradanahalli C. Guru; Judy S. Crabtree; Kevin D. Brown; Karen J. Dunn; Pachiappan Manickam; Nijaguna B. Prasad; Danny Wangsa; A. Lee Burns; Allen M. Spiegel; Stephen J. Marx; William J. Pavan; Francis S. Collins; et al. (Mammalian Genome, 1999)

The effects of serial passage of a nucleopolyhedrosis virus through an alternate host system - O. H. Pavan; D. G. Boucias; J. C. Pendland (BioControl, 1981)